Pest categorisation of Colletotrichum gossypii. (1st June 2018) - ; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: The Panel on Plant Health performed a pest categorisation of Colletotrichum gossypii, the fungal agent of anthracnose and ramulosis diseases of cotton, for the EU. The identity of the pest is well established and reliable methods exist for its detection/identification. The pest is present in most of the cotton‐growing areas worldwide, including Bulgaria and Romania in the EU. Colletotrichum gossypii is listed as Glomerella gossypii in Annex IIB of Directive 2000/29/EC and is not known to occur in Greece, which is a protected zone (PZ). The only hosts are Gossypium species, with G. hirsutum and G. barbadense being the most susceptible. The pest could potentially enter the PZ on cotton seeds originating in infested third countries or EU infested areas. Entry into PZ by natural means from EU infested areas is possible, although there is uncertainty on the maximum distance the pest can travel by wind or insects. Bolls and unginned cotton are minor pathways of entry. Pest distribution and climate matching suggest that the pest could establish and spread in cotton‐producing areas of northern Greece. In the infested areas, the pest causes damping‐off, leaf/boll spotting, boll rot, witches' broom symptoms and stunting resulting in yield and quality losses. It affects also the lint and seeds reducing fibres quality and seed germinability. It is expected that its introduction and spread in the EU PZ would impact cotton yield and quality. The agricultural practices and control methods currently applied in Greece would not prevent pest establishment and spread. Colletotrichum gossypii meets all the criteria assessed by EFSA for consideration as potential quarantine pest for the EU PZ of Greece. The criteria for considering C. gossypii as a potential Union regulated non‐quarantine pest are also met since cotton seeds are the main means of spread.